USM AND TSU RUSSIA TO EXPAND RESEARCH COLLABORATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
TOMSK, 26 May 2015 – Universiti Sains Malaysia (USM) and Tomsk State University (TSU), Russia will explore the possibility of extending research collaboration and offering joint degrees at postgraduate level in selected areas of mutual strength and expertise. This was stated by USM Deputy ViceChancellor (Research & Innovation), Professor Dato’ Dr. Muhamad Jantan at a meeting with the Rector of TSU, Professor Dr. Eduard V. Galazhinskiy here today.